Dynamics of physical capabilities and technical preparedness of cadets (U16) from "Shumen" basketball club - Simeonova, T.; Yankov, Y.; Stoychev, C. (2nd International scientific conference "Sport, recreation, health", 12th & 13th May, 2017, Belgrade, 2017)
Basketball is one of the most widely practiced sports. Practicing basketball creates conditions for the development of qualities such as speed, strength, agility, quickness, endurance, flexibility and accuracy. The modern perception of the game requires a high level of physical preparation, brilliant technique with and without the ball and an extensive tactical training consistent with the individual characteristics of the players. The present research studies the changes in the physical and tactical preparedness of the cadet basketball players, 15 to 16 years of age, who are members of basketball club "Shumen". The physical abilities of the cadets are assessed through tests on 20m run, shuttle run, standing vertical jump and triple jump. Based on their physical shape, the boys build and master their technical skills. The technical parameters dribble and shooting are of great importance to the preparation. They are examined with the help of the following tests: figure eight dribble, ball handling index, shooting on the move and shooting from a standing position. These eight indicators are examined for a period of two competitive years. The dynamics of the indicators through which the boys are tested will be of good help for the development of the physical and technical preparedness of the boys from the sports club.